Measurement of Face Detection Accuracy Using Intensity Normalization Method and Homomorphic Filtering - I Nyoman Gede Arya Astawa; I Ketut Gede Darma Putra; I Made Sudarma; Rukmi Sari Hartati (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
One of the factors that affects the detection system or face recognition is lighting. Image color processing can help the face recognition system in poor lighting conditions. In this study, homomorphic filtering and intensity normalization methods used to help improve the accuracy of face image detection. The experimental results show that the non-uniform of the illumination of the face image can be uniformed using the intensity normalization method with the average value of Peak Signal to Noise Ratio (PSNR) obtained from the whole experiment is 22.05314 and the average Absolute Mean Brightness Error (AMBE) value obtained is 6.147787. The results showed that homomorphic filtering and intensity normalization methods can be used to improve the detection accuracy of a face image.